PENGARUH STRATEGI PEMBELAJARAN BERBASIS SELF REGULATED LEARNING DAN PENGETAHUAN AWAL TERHADAP HASIL BELAJAR - Yowelna Tarumasely (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2020)
Abstrack: This study aims to analyze the effect of self-regulated learning-based learning and initial knowledge on learning outcomes for the second semester of Christian Religious Education students. The research subjects were 96 people who were divided into two groups, namely the experimental and control groups. Data obtained by using tests to measure learning outcomes. Data analysis used two-way ANOVA. The results show that there are differences in learning outcomes between self-regulated learning and teacherregulated learning-based learning strategies with high and low initial knowledge levels, and there is an interaction between learning strategies and initial knowledge on learning outcomes. This means that selfregulated learning-based learning and prior knowledge have a better effect on the results of the Learning Theory Key Words: Self Regulated Learning Strategy, Initial Knowledge, Learning Outcomes